2007
DOI: 10.1139/x07-040
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and calcium additions increase forest growth in northeastern USA spruce–fir forests

Abstract: We determined responses of red spruce ( Picea rubens Sarg.) – balsam fir ( Abies balsamea (L.) Mill.) forests to 6 years of nitrogen (N), calcium (Ca), and N + Ca treatments (100, 160, and 260 kg·ha–1·year–1 of N, Ca, and N + Ca, respectively) in New York (NY) and New Hampshire (NH). Forest responses to Ca treatments were also determined in Vermont (VT). Nitrogen treatments increased aboveground net primary production (ANPP) by 33% and 25% above controls in NY and NH, respectively. Similarly, N + Ca treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…b and ) but vary three‐fold in their responses to N enrichment, corroborating evidence that continued anthropogenic increases in soil N will lead to greater community productivity (Kulmatiski et al. , LeBauer and Treseder ) and lower species richness through competitive exclusion of less nitrophilic species (Bobbink et al. , De Schrijver et al.…”
Section: Discussionsupporting
confidence: 58%
“…b and ) but vary three‐fold in their responses to N enrichment, corroborating evidence that continued anthropogenic increases in soil N will lead to greater community productivity (Kulmatiski et al. , LeBauer and Treseder ) and lower species richness through competitive exclusion of less nitrophilic species (Bobbink et al. , De Schrijver et al.…”
Section: Discussionsupporting
confidence: 58%
“…Within this same watershed, Green et al (2013) found that stream flow was increased due to reduced rates of evapotranspiration for three years, before returning to pre-treatment levels. They attributed this to increased aboveground productivity due to the short term correction of a nutrient imbalance, as found in other studies (e.g., Kulmatiski et al, 2007).…”
supporting
confidence: 68%
“…Magill et al ., ), decreasing total photosynthetic surface area (e.g. Kulmatiski et al ., ), modifying tissue allocation patterns (e.g. Talhelm et al ., ), or increasing allocation of C from photosynthesis to acquire N from the environment (e.g.…”
Section: How Does N Limitation Occur At the Individual Scale?mentioning
confidence: 99%